2014
DOI: 10.1002/cncy.21414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine cytology and fluorescence in situ hybridization in upper urothelial tract samples

Abstract: BACKGROUND:The cytologic diagnosis of urothelial carcinoma (UC) of the upper urothelial tract (UT) is challenging.Using the UroVysion probe set adds diagnostic value for the detection of bladder cancer in voided urine. In instrumented Biopsy confirmation of UTUC in 21 patients was considered the gold standard. RESULTS: Cytology alone was found to be poorly sensitive (38%) but highly specific (89%) for the detection of UTUC. FISH was found to increase the sensitivity of cytology and decrease specificity. Tetras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…This difference may be due to the fact that the majority of patients in the cohort analyzed by Huang et al (17) exhibited high-grade UTUCs, for which the FISH assay has higher sensitivity than for low-grade tumors (17,20). The sensitivity of FISH for the detection of UTUC identified in the present study was similar to that reported by Gruschwitz et al (21), but higher than that reported by Reynolds et al (9). There is a possible reason for this difference.…”
Section: C B Asupporting
confidence: 69%
See 3 more Smart Citations
“…This difference may be due to the fact that the majority of patients in the cohort analyzed by Huang et al (17) exhibited high-grade UTUCs, for which the FISH assay has higher sensitivity than for low-grade tumors (17,20). The sensitivity of FISH for the detection of UTUC identified in the present study was similar to that reported by Gruschwitz et al (21), but higher than that reported by Reynolds et al (9). There is a possible reason for this difference.…”
Section: C B Asupporting
confidence: 69%
“…Suspicious cytology was defined as those samples that contained cells with morphologies that could not be clearly classified as tumor or normal cells. Histopathological classification was performed according to the Union for International Cancer Control criteria (8,9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bubendorf et al (32) suggested that the detection of ≤4 tetrasomic cells in each sample should be considered normal in order to improve diagnostic value. Concurrently, Reynolds et al (33) demonstrated that FISH had improved sensitivity vs. cytology, but decreased specificity due to a greater number of false-positive results. Considering the lack of validation of the UroVysion criteria in the Chinese population, the threshold was determined by performing FISH assays on samples from healthy donors.…”
Section: Discussionmentioning
confidence: 99%